Strengthening the Ethics of the Deontology of Local Media Journalists in the Disruption Era - Mubarok, Mubarok; Sarwono, Billy K.; Angeliqa, Fitria (Universitas Semarang, 2023)
Introduction: This study aims to describe the important role of organizational culture in strengthening the deontology ethics of local media journalists. Deontological ethics states that the will to do good must arise from within a person's individual. Organizational culture is one of the means used to instill, strengthen and internalize these values. Technological disruptions that have an impact on changes in media consumption, the closure of print media, the development of online media have changed the dynamics of journalistic practice in Indonesia. The important role of ethics comes to the fore in maintaining the quality of local media journalistic practices. Methods: This research was conducted with a phenomenological approach. The data were obtained from interviews with local media journalists in Central Java. Informants in this study are journalists who have worked for more than 20 years in local media, members of journalist organizations and actively provide journalistic ethics training. Findings: Ethics are still considered important by journalists. Therefore, it is necessary to strengthen ethics considering that not all journalists have adequate knowledge and understanding of ethics. The culture of media organizations and professional organizations plays an important role in strengthening the deontology ethics of local media journalists. Originality: This research provides a novelty on how to strengthen the deontological ethics of local media journalists through strengthening organizational culture. This research provides it in terms of building journalist ethics as individuals and the media as a press company that sells news ideology.